One-pot multistep mechanochemical synthesis of fluorinated pyrazolones - Howard, Joseph L.; Nicholson, William; Sagatov, Yerbol; Browne, Duncan L. (Beilstein Journal of Organic Chemistry, 2017)
Solventless mechanochemical synthesis represents a technique with improved sustainability metrics compared to solvent-based processes. Herein, we describe a methodical process to run one solventless reaction directly into another through multistep mechanochemistry, effectively amplifying the solvent savings. The approach has to consider the solid form of the materials and compatibility of any auxiliary used. This has culminated in the development of a two-step, one-jar protocol for heterocycle formation and subsequent fluorination that has been successfully applied across a range of substrates, resulting in 12 difluorinated pyrazolones in moderate to excellent yields.
Keywords: fluorination; heterocycles; mechanochemistry; multistep; solid-state synthesis

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Ranu, B.; Stolle, A. (Royal Society of Chemistry, 2014)

(untitled) - Kaupp, G. (CrystEngComm, 2011)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Rodríguez, B.; Bruckmann, A.; Rantanen, T.; Bolm, C. (Adv. Synth. Catal., 2007)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Hayashi, Y. (Chem. Sci., 2016)

(untitled) - Tyagi, M.; Khurana, D.; Kartha, K. P. R. (Carbohydr. Res., 2013)

(untitled) - Konnert, L.; Dimassi, M.; Gonnet, L.; Lamaty, F.; Martinez, J.; Colacino, E. (RSC Adv., 2016)

(untitled) - Zhao, Y.; Rocha, S. V.; Swager, T. M. (J. Am. Chem. Soc., 2016)

(untitled) - Hernández, J. G.; Butler, I. S.; Friščić, T. (Chem. Sci., 2014)

(untitled) - Friščić, T.; Childs, S. L.; Rizvi, S. A. A.; Jones, W. (CrystEngComm, 2009)

(untitled) - Hasa, D.; Miniussi, E.; Jones, W. (Cryst. Growth Des., 2016)

(untitled) - Do, J.-L.; Mottillo, C.; Tan, D.; Štrukil, V.; Friščić, T. (J. Am. Chem. Soc., 2015)

(untitled) - Howard, J. L.; Sagatov, Y.; Repusseau, L.; Schotten, C.; Browne, D. L. (Green Chem., 2017)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D. (J. Fluorine Chem., 2006)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - O’Hagan, D. (J. Fluorine Chem., 2010)

(untitled) - Jeschke, P. (ChemBioChem, 2004)

(untitled) - Howard, J. L.; Schotten, C.; Alston, S. T.; Browne, D. L. (Chem. Commun., 2016)

Synthetic Methods in Drug Discovery - Browne, D. L.; Richardson, P. (Fluorination Approaches, 2016)

(untitled) - Browne, D. L. (Synlett, 2015)

(untitled) - Surmont, R.; Verniest, G.; De Kimpe, N. (Org. Lett., 2010)

(untitled) - Skinner, P. J.; Cherrier, M. C.; Webb, P. J.; Shin, Y.-J.; Gharbaoui, T.; Lindstrom, A.; Hong, V.; Tamura, S. Y.; Dang, H. T.; Pride, C. C.; Chen, R.; Richman, J. G.; et al. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Dressen, D.; Garofalo, A. W.; Hawkinson, J.; Hom, D.; Jagodzinski, J.; Marugg, J. L.; Neitzel, M. L.; Pleiss, M. A.; Szoke, B.; Tung, J. S.; Wone, D. W. G.; Wu, J.; et al. (J. Med. Chem., 2007)

(untitled) - Sloop, J. C.; Jackson, J. L.; Schmidt, R. D. (Heteroat. Chem., 2009)

(untitled) - Breen, J. R.; Sandford, G.; Patel, B.; Fray, J. (Synlett, 2015)